MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT PADA KETERAMPILAN MENULIS KALIMAT SEDERHANA BAHASA PERANCIS - Ananda, Novira Putri; Sunendar, Dadang; Sopiawati, Iis (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2024)
This study aims to (1) describe the steps of implementing the Teams Games Tournament (TGT) cooperative learning model in the skill of writing simple sentences in French; (2) describe the results of students' ability to write simple sentences after implementing the TGT cooperative model; and (3) inform students' responses to the TGT cooperative learning model.The study used a pre-experimental method with a one-shot case study design. The research instruments included observation sheets for researcher and student activities, a test of simple French sentence writing skills, and a questionnaire. The sample consisted of 30 students at one of the SMKN in Bandung City. The results of the study showed that the treatment stages included: presenting material, dividing students into 6 teams of 5 people, facilitating group discussions, providing games in the form of simple sentence writing skill exercises, summarizing student scores and writing test results on the board, and giving awards to groups.The test results showed an average score of students' simple French sentence writing skills of 8.83 with a mastery level of 8.83% which is included in the good criteria. This shows that the TGT type cooperative learning model can help students achieve good French simple sentence writing skills. The results of the questionnaire showed that 96.67% of students liked learning French with the TGT type cooperative learning model, 86.67% felt helped in improving their French language skills through French simple sentence writing skills, and more than 96.66% felt enthusiastic about learning French with the TGT type cooperative learning model. Thus, this TGT type cooperative learning model can be used as an alternative in language teaching, especially French simple sentence writing skills.